Strategic learning for industry readiness: a case study of the industrial mentorship model in risk and takaful education / Fauzilah Salleh and Nur Salina Ismail - Salleh, Fauzilah; Ismail, Nur Salina (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
Mentorship has long been recognized as a crucial component of a successful academic journey. Despite the growing popularity of formal mentoring programs in educational institutions, there is a scarcity of empirical research on how to design these programs for optimal effectiveness. The “Loss and Control Seminar” represents a culminating requirement for undergraduate students that offers a comprehensive opportunity to apply their knowledge on risk management to real-world business challenges. However, the current approach to this course primarily relies on academic literature and lacks industry input, thus, hindering students from aligning their findings with industry expectations. This study sought to introduce the “Industrial Mentorship Model (IMM)” into the Loss and Control Seminar to better equip undergraduates for the competitive job market. This qualitative study comprised three phases, namely introduction, implementation, and evaluation, involving 61 students and twelve industrial mentors. Key findings demonstrated that the IMM fostered relationships that empowered mentees to acquire knowledge and skills, established valuable networks, enhanced self-confidence, and cultivate self-reflective abilities. In addition, mentors derived personal satisfaction and gained insights into their own learning processes through their involvement in the program.